Ameliorating potency of Chenopodium album Linn. and vitamin C against mercuric chloride-induced oxidative stress in testes of Sprague Dawley rats - Sarwat Jahan; Tayyaba Azad; Amina Ayub; Asad Ullah; Tayyaba Afsar; Ali Almajwal; Suhail Razak (Komiyama Printing Co. Ltd, 2019)
Abstract Background Mercury has been documented as an industrial risk that posed a serious danger to human health. Mercury exposure results in oxidative stress that may lead to the pathogenesis of male reproductive dysfunction. The present study investigated the ameliorating potential of Chenopodium album L. and vitamin C against mercuric chloride-induced oxidative deterioration of reproductive functions in adult male rats. Methods Group 1 (control) received saline. Group 2 received Mercury (0.15 mg/kg b.w, i.p) dissolved in distilled water. Groups 3 and 4 were given oral gavage of vitamin C (200 mg/kg b.w) and the ethanolic extract of C. album (200 mg/kg b.w) respectively, along with Mercury (0.15 mg/kg b.w, i.p). Group 5 was treated only with C. album (200 mg/kg b.w). After 30 days of the treatment, the rats were dissected and their testicular tissue and the cauda epididymis were used for biochemical analysis while blood plasma was used for protein determination. Results The applied dose-treatment of Mercury-induced oxidative stress in the testis and cauda epididymis tissues of the rats was apparent by a noteworthy decrease in total protein, CAT, SOD, POD, and GST values while there was increase in ROS and TBARS levels. Furthermore, Mercury decreases daily sperm production and enhanced sperm DNA damage as noticeable by an increase in the head and tail length of comets and decrease in intact DNA. There was no significant effect on the body weight and the weight of the reproductive tissues. Treatment with C. album significantly ameliorated the total protein, ROS, and TBARS content. Similarly, the level of CAT, SOD, POD, and GST was significantly improved and the daily sperm production was significantly increased. Furthermore, C. album administration significantly protected Mercury-induced sperm DNA damage. The results of the extract treatment group were compared with those of vitamin C in detoxifying the oxidative stress and restoring the sperm parameters. Conclusion C. album showed protection against Mercury-induced oxidative stress by ameliorating antioxidant enzyme activity, daily sperm production, and DNA damage in rat testes. This suggests that C. album could be beneficial against toxicity induced by an environmental toxicant.